Mobility, ICT, and health: a built environment investigation of older Chinese migrants’ social isolation and loneliness - Amber DeJohn; Bochu Liu; Xinlin Ma; Michael J. Widener; Zhilin Liu (BMC Public Health)
Abstract Background Social isolation and loneliness have detrimental impacts on health, especially for older adults. During the COVID-19 pandemic, physical access to third places (e.g., coffee shops, libraries) decreased due to the closure of non-essential destinations and personal risk assessments. Older adults reported adopting information and communication technology (ICT) during pandemic lockdowns. ICT-mediated socializing may have different impacts on loneliness than in-person equivalents. Understanding access to social connection and their distinct relationships to the built environment and health for older Chinese migrants is critical to supporting equitable, healthy aging in a post-COVID world. Methods Using a survey of older Chinese migrants in the Greater Toronto Area (GTA) during the extended COVID-19 lockdown, we investigate how community mobility and ICT use, two mechanisms of socializing, relate to the built environment and influence loneliness (De Jong Gierveld 6-item scale), as well as mental and physical health (SF-12). Specifically, we use a structural equation model to test a theoretical framework of older adult social isolation. Results Our model demonstrates the importance of community mobility for reducing feelings of loneliness, while ICT use is significantly related to better physical health. Both community mobility and ICT use have significant, although opposite, relationships to transit density. Conclusions Results indicate that ICT use might have limited ability to reduce loneliness and support mental health when mobility is limited. Addressing older migrants’ barriers to community mobility is critical to reducing feelings of loneliness.